2022
DOI: 10.1371/journal.ppat.1010818
|View full text |Cite
|
Sign up to set email alerts
|

The inclusion membrane protein IncS is critical for initiation of the Chlamydia intracellular developmental cycle

Abstract: All Chlamydia species are obligate intracellular bacteria that undergo a unique biphasic developmental cycle strictly in the lumen of a membrane bound compartment, the inclusion. Chlamydia specific Type III secreted effectors, known as inclusion membrane proteins (Inc), are embedded into the inclusion membrane. Progression through the developmental cycle, in particular early events of conversion from infectious (EB) to replicative (RB) bacteria, is important for intracellular replication, but poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Analysis of the samples by mass spectrometry revealed the presence of the C. trachomatis inclusion membrane protein CTL0402 in the coimmunoprecipitate of the infected samples. We have recently renamed CTL0402 IncS Ct ( 29 ); this nomenclature will be used here. To confirm the inclusion localization of endogenous IncS Ct , HeLa cells infected with wild-type C. trachomatis for 24 h were fixed and stained with anti-IncS antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analysis of the samples by mass spectrometry revealed the presence of the C. trachomatis inclusion membrane protein CTL0402 in the coimmunoprecipitate of the infected samples. We have recently renamed CTL0402 IncS Ct ( 29 ); this nomenclature will be used here. To confirm the inclusion localization of endogenous IncS Ct , HeLa cells infected with wild-type C. trachomatis for 24 h were fixed and stained with anti-IncS antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated whether IncS Ct was necessary for STIM1 association with C. trachomatis inclusion. However, we recently showed that a C. trachomatis incS Ct mutant does not progress through the early stages of the C. trachomatis developmental cycle ( 29 ). To bypass the early developmental defect of the incS Ct mutant, we capitalized on the fact that the severe growth defect of the C. trachomatis incS Ct mutant can be complemented by inducing incS Ct transcription during the first 6 to 8 h p.i.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations